Orally Administered Koumine Persists Longer in the Plasma of Aged Rats Than That of Adult Rats as Assessed by Ultra-Performance Liquid Chromatography-Tandem Mass Spectrometry - Ye, Li-Xiang; Xu, Ying; Zhang, Shui-Hua; Cao, Da-Xuan; Chen, Ling-Fan; Su, Yan-Ping; Huang, Hui-Hui; Yu, Chang-Xi (Frontiers in Pharmacology, 2020)
Aging leads to changes in nearly all pharmacokinetic phases. Koumine (KM), an alkaloid derived from Gelsemium elegans Benth., is effective against age-associated chronic diseases, but its dose proportionality following oral administration in aged individuals remains unknown. Herein, we established and validated a simple method that requires low sample volumes to determine KM concentration in rats using ultra-performance liquid chromatography-tandem mass spectrometry. The maximum plasma concentration (Cmax) of 7 mg·kg−1 KM was ~12-fold and ~24-fold higher than that of 0.28 mg·kg−1 KM in adult and aged rats, respectively (P < 0.01). Time to reach Cmax (Tmax) for 7 mg·kg−1 KM was 23% longer in aged rats (P < 0.05). The area under the curve (AUC) of 7 mg·kg−1 KM was >17-fold and >43-fold higher than those of 0.28 mg·kg−1 KM in adult and aged rats, respectively (P < 0.01). The half-life (t1/2) of 7 mg·kg−1 KM was over 4-fold longer than that of 0.28 mg·kg−1 KM in adult rats (P < 0.01). The t1/2 of 1.4 and 7 mg·kg−1 KM were 1.5~2-fold longer, than that of 0.28 mg·kg−1 KM in aged rats (P < 0.05). The clearance rate of 7 mg·kg−1 KM was significantly lower in aged than in adult rats (P < 0.05). For 7.0 mg·kg−1 KM, the Cmax in aged rats was higher than in adult rats during the Tmax period (P < 0.05). In aged rats, the AUC for KM was >2.5-fold higher (P < 0.05) and the t1/2 was >60% longer than in adult rats (P < 0.05). These results help interpret the pharmacokinetics of KM in aging-associated diseases.